Reverdin pinch grafts for surgical closure after removal of nonmelanoma skin cancer lesions of the leg - Frank Hofmann; Ammar Faisal Hameed; Thomas Schleussinger; Field Lawrence (Wolters Kluwer Medknow Publications, 2018)
Background: Surgical closure after removal of nonmelanoma skin cancer on the leg can be challenging. Objective: Reverdin pinch grafting is an old skin transplant approach to treat leg ulcers. We present our experience using Reverdin pinch graft to close leg surgical defects following excision of nonmelanoma skin cancers. Patients and Methods: This was a retrospective study of 35 patients with medium-large sized defects with a median ± standard deviation of 20 ± 2.7 mm. Pinch grafts harvested from the thigh were used to cover the surgical leg defects with a 6-year follow-up period. Results: The average healing time after pinch grafting was 4 weeks ± 1.12 weeks. Ten patients (28.6%) had a failure of one or two single pinch grafts. There was no hypertrophic or keloid scarring in any grafted patients. Wound infection occurred in two patients (5.7%) and postoperative hemorrhage in only one patient (2.8%). Basal cell carcinoma arose in one patient (2.8%). Conclusion: Reverdin pinch graft technique is an easy and effective closure option for medium-large surgical defects of the leg after nonmelanoma skin cancer excision.